Digital Transformation in Information Management: Challenges and Strategic Implementation - Dedy Sofian MZ; Angga Radlisa Samsudin; Sunardi Sunardi (CV. Global Cendekia Inti, 2026)
Digital transformation has emerged as a strategic phenomenon driving substantial changes in organizational information management. This study aims to identify key challenges and analyze implementation strategies for digital transformation within information management practices. A qualitative approach was employed through a literature-based study, utilizing thematic analysis of relevant scholarly sources. The findings indicate that the primary challenges of digital transformation encompass structural, technological, and cultural dimensions, which interact dynamically and influence implementation effectiveness. On the other hand, digital transformation contributes positively to improving information quality, enhancing system efficiency, and enabling data-driven decision-making. However, these benefits are not automatic; they are highly contingent upon the quality of information governance and the organizational readiness to adopt digital technologies strategically. Furthermore, this study identifies several effective implementation strategies, including the integration of knowledge management, the strengthening of digital leadership, the application of change management practices, and the continuous evaluation of information systems. Based on these findings, a conceptual model is proposed, positioning information management and knowledge management as mediating variables in the relationship between digital transformation and organizational performance. This study contributes theoretically to the advancement of digital-based information management research and offers practical implications for organizations in designing more adaptive and sustainable digital transformation strategies.